Ductal carcinoma in situ and intraoperative partial breast irradiation: Who are the best candidates? Long-term outcome of a single institution series. (April 2019) - Leonardi, Maria Cristina; Corrao, Giulia; Frassoni, Samuele; Vingiani, Andrea; Dicuonzo, Samantha; Lazzeroni, Matteo; Fodor, Cristiana; Morra, Anna; Gerardi, Marianna Alessandra; Rojas, Damaris Patricia; Dell'Acqua, Veronica; Marvaso, Giulia; et al.
Highlights: Analysis of the outcome of 180 DCIS patients treated with intraoperative electrons. The whole population showed high local relapse rate, increasing over time. Suitable Group, according to ASTRO APBI, showed a 5-year local relapse rate of 11%. Pathological characteristics were not sufficient to select low risk group. Integration with biomolecular factors (ER/PgR and HER2 receptors) is needed. Abstract: Aims: To report the long-term outcome of a single institution series of pure ductal carcinoma in situ (DCIS) treated with accelerated partial irradiation using intraoperative electrons (IOERT). Methods: From 2000 to 2010, 180 DCIS patients, treated with quadrantectomy and 21 Gy IOERT, were analyzed in terms of ipsilateral breast recurrences (IBRs) and survival outcomes by stratification in two subgroups. The low-risk group included patients who fulfilled the suitable definition according to American Society of Radiation Oncology (ASTRO) Guidelines (size ≤2.5 cm, grade 1–2 and surgical margins ≥3 mm) (Suitable), while the remaining ones formed the high-risk group (Non-Suitable). Results: Eighty-four and 96 patients formed the Suitable and Non-Suitable groups, respectively. In the whole population, the cumulative incidence of IBR at 5, 7 and 10 years was 19%, 21%, and 25%, respectively. In the Suitable group, the cumulative incidence of IBR remained constant at 11% throughout the years, while in the Non-Suitable group increased from 26% at 5 years to 36% at 10 years ( p < 0.0001). When hormonal positivity and HER2 absence of expression were added to the selection of the Suitable group, the cumulative incidence of IBR dropped and stabilized at 4% at 10 years. None died of breast cancer. In the whole population, 5-year and 10-year overall survival rate was 98% and 96.5%, respectively, without any difference between the two groups. Conclusions: The overall and by group IBR rates were high and stricter criteria are required for acceptable local control for Suitable DCIS. Because of the concerns raised, IOERT should not be used in clinical practice.